Intramuscular oxytocin 10 units versus intravenous methylergometrine 0.2 mg in active management of third stage of labour for prevention of postpartum haemorrhage: a comparative study - Narayana, Divya; Pathak, B.; Khurana, Abha; Kohli, Uttara Aiyer (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: To compare the effectiveness of 10 IU of oxytocin IM with 0.2 mg methyl ergometrine IV in the prevention of post-partum hemorrhage when used as a part of active management of third stage of labour. This study aims to compare their influence on duration of the third stage of labour, the amount of blood loss during the third stage of labour and the immediate post-partum period and side effects of the drugs if any. Methods: The study was conducted in a tertiary care teaching hospital. 200 women, who underwent normal delivery with or without episiotomy, were enrolled and were randomly distributed into two groups. 100 women received 10 IU of intramuscular Oxytocin and 100 women received intravenous 0.2 mg of methyl ergometrine. Women of both the groups were given the medication after delivery of anterior shoulder of the baby. Comparison done between percentages fall in Hb from before delivery to 24 hours after delivery, need for additional uterotonic agents, need for blood transfusion, duration of third stage of labour and any side effects including retained placenta and need for manual removal of placenta. Results: Intravenous methylergometrine was observed to be equally effective as intramuscular oxytocin in prevention of post-partum hemorrhage. There was no difference in the duration of third stage of labour, amount of blood loss, need for additional uterotonic agents, and need for blood transfusion in both the groups. There was no significant side effect in both the groups. Conclusions: Intramuscular oxytocin is as efficacious as Intravenous methylergometrine in the prevention of postpartum hemorrhage with no side effects.